मालवी संस्कृति और साहित्य - Rajpurohit, Bhagawatilal (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad)
This book is a critical analysis of Malvi culture and literature. It describes the features of various arts and culture of Malva region.
Malvi Sanskriti aur Sahitya
Keywords: मालवी संस्कृति और साहित्य; Malvi Sanskriti aur Sahitya; Folk Culture; Hindi; Hindi; Malvi